Kajian Lokasi Pasar Rakyat Payakumbuh II di Kecamatan Payakumbuh Utara - Gilang Satrya Purnama (JURNAL BUANA, 2022)
The location of the people's market is very crucial in accelerating economic growth in an area. Functional and optimization of the people's market is a study that needs to be discussed because in terms of location selection it should be established in a suitable location. This study aims to investigate the suitability of the location of the Payakumbuh II people's market in North Payakumbuh District, Payakumbuh City. The approach in this research is quantitative using buffering technique. The residents' market is divided into an elaboration of the area & capacity of traders, namely B-III in the Payakumbuh II people's market. Classification of the people's market B-III which has a smaller area and trading capacity. The suitability of the people's market from the affordability of chemical warehouse factories, gas stations, settlements,. The results showed that the location of the people's market in North Payakumbuh District was synchronized from the location. This relates to the proximity and achievability of settlements.